The digital archives handbook a guide to creation, management, and preservation - Purcell, Aaron D., 1972- (Rowman & Littlefield, 2019)
"This edited volume explores the challenges of digital donations with essays from archivists who have developed methods to provide access to a diverse range of digital materials found in government, private, and academic archives"--